2013 Social Accounting Matrix for Ghana: A Nexus Project SAM - Ghana Statistical Service; Institute for Statistical, Social and Economic Research; International Food Policy Research Institute (International Food Policy Research Institute, 2017)
The purpose of this paper is used to document the different steps followed to construct the 2013 Social Accounting Matrix for Ghana. The SAM is an extension of the Standard Nexus Structure. It consists of 55 activity sectors, 56 commodity sectors, three types of factors of production: labor (rural and urban disaggregated by level of education), land, and capital (disaggregated by crops, livestock, mining and other sectors). The household sector is divided spatially into urban and rural households. Rural households are further disaggregated into households that earn crop and/or livestock incomes (i.e., farm households) and those that do no earn incomes from either source (i.e., nonfarm households). Households are further disaggregated into per capita expenditure quintiles. This SAM allows analyzing issues at the detailed level and to better understand the potential impacts of policy changes for both better off and more vulnerable households.